Transmission and Characterization of Creutzfeldt–Jakob Disease and Chronic Wasting Disease in the North American Deer Mouse - Jennifer Myskiw; Lise Lamoureux; Kathy Frost; Rebecca Fox; Jessy A. Slota; Gordon Mitchell; Ben A. Bailey-Elkin; Stephanie A. Booth (Viruses)
Prion transmission into rodents is essential for understanding prion strains. However, it is often limited by a “species barrier” that makes transmission challenging and complicates the study of animal and human prion diseases. Here, we report that North American deer mice (Peromyscus maniculatus) are susceptible to infection with both human sporadic Creutzfeldt–Jakob disease (sCJD) and chronic wasting disease (CWD). Experimental transmission of both sCJD and CWD in deer mice resulted in 100% attack rates, albeit with differing incubation times, with CWD-inoculated mice taking nearly three times longer than sCJD-inoculated mice to succumb. We observed distinct patterns of spongiform vacuolation and prion-protein deposition in the brain, as well as distinct protein-glycosylation profiles and seeding kinetics in RT-QuIC for each strain. Adaptation on the second passage led to reduced incubation periods and marked strain-specific pathology, as seen predominantly in the cortex in sCJD and the thalamus in CWD. Notably, primary transmission of CWD resulted in infrequent vacuoles and widespread punctate deposits of prion protein in the brain, while diffuse staining and remarkable vacuolation of the thalamus were seen on passage. Prion seeding kinetics for sCJD and CWD were indistinguishable in the second passage; however, the distinct glycosylation patterns seen on immunoblot of the prion protein were maintained. Adaptation also resulted in extraneural dissemination of prion seeding activity distinct to CWD infection. Overall, the ability to transmit both CWD and sCJD to this model, resulting in clear differences in incubation period, biochemical properties, clinical signs, pathology and seeding kinetics, indicates that the model has the potential for use as a tool to investigate atypical cases of sCJD that may indicate CWD spillover to humans.